Case Report: The Sexual Experiences of Forensic Mental Health Patients - Brand, Elnike; Ratsch, Angela; Heffernan, Edward (Frontiers in Psychiatry, 2021)
The recovery-based approach to forensic mental health rehabilitation is to support the patient to achieve a fulfilling life—a principle which should include achieving a fulfilling sexual life. This paper presents four vignettes from forensic mental health patients. The four cases demonstrate the omission, avoidance and then judgement by forensic mental health clinicians around the intimate and sensitive, yet important domain of the patient's sexual life. The cases illustrate that gap in the clinical domain and demonstrate the requirement for forensic mental health clinicians to have a greater awareness, acknowledgment, and assessment of their patient's sexuality and sexual health needs. Incorporating sexual health into standard clinical assessments will contribute to improved patient management in addition to supporting the principles of holistic forensic mental health recovery and rehabilitation.